The language features used by Indonesian food-vloggers of different genders - N R Thiffanah Thuffailah; Eri Kurniawan; Ernie D. A. Imperiani (Universitas Pendidikan Indonesia (UPI), 2020)
This study aims to examine the language features used by Indonesian food-vloggers of different genders as well as the functions of each feature in their utterances. Six Indonesian food-vloggers of different genders were selected as the data. This study used a descriptive qualitative method and differential language analysis to analyse the data. The results show that out of seven features, there were only six features that have classified as women and men’s language features used by both women and men food-vloggers; namely, lexical hedges (30 times in women utterances and 40 times in men utterances), followed by compliment (25 in women utterances and 15 times in men utterances), command and directives (13 times in women utterances and 14 times in men utterances), swear and taboo words (14 times in women utterances and 11 times in men utterances), question (11 times in women utterances and 9 times in men utterances), tag question (6 times in women utterances and 11 times in men utterances) and no minimal response feature is found. Regarding functions, the food-vloggers use hedging to damp down the statement force; say positive compliment to show satisfaction; give command and direct to make the interaction done properly; swear to show dissatisfaction; ask questions to make their viewers more involved in the interactions; use tag questions to confirm what the speakers have said. The findings show that males tend to be the dominant ones who applied the language features compared to the females’ food-vloggers. This may be due to the image of men in the society which is depicted as the masculine one, and to have masculine character means that they have to perform it. Therefore, these male food-vloggers make sure that their character as the food-vloggers could match with the viewers' expectations of how good vloggers should be, and one of the strategies is by communicating well enough with the viewers by using the language features. Keyword: Food-vlogger; gender; language features